Produksi dan uji aktivitas enzim fatty acid photodecarboxylase dari Chlorella variabilis melalui kultivasi pada medium CYT dan KW21 - Yora FARAMITHA; Sheren Prajna PARAMITA; Fauziatul FITRIYAH; Djoko SANTOSO; Irma KRESNAWATY (E-Journal Menara Perkebunan, 2022)
Chlorella variabilis is the microalgae that produce fatty acid photodecarboxylase (CvFAP) enzymes which can catalyze the decarboxylation of long chain fatty acids into hydrocarbons through a process that is influenced by blue light. However,  CvFAP enzyme content in C. variabilis is relatively small and the ability of the enzyme as a biocatalyst needs to be optimized. This study aims to compare the effect of C. variabilis microalgae cultivation medium types, particularly: 1) C medium, yeast extract, and tryptone (CYT medium), and 2) KW21 medium which is a commercial marine algae culture medium, on microalgae growth and the resulting protein. In addition, the CvFAP enzyme extract from each medium was proven for its ability to convert long-chain fatty acids into pentadecane by optimizing variations in substrate type, enzyme concentration, and incubation time. C. variabiliswas cultivated for 2-3 weeks with a ratio of light and dark lighting time of 8:16 (hours/hours). The protein content of C. variabilis was determined using the Lowry method. Proteins were extracted physico-chemically and enzyme activity assay were carried out under conditions of exposure to blue light. The pentadecane content formed from the enzyme activity assay was measured using GC-MS. The study results showed that microalgae growth and protein content of C. variabilis were higher in the CYT medium compare to those in KW21 medium. The protein band appears at 67-68 kDA whichis speculated to affect the ternary complex bond between FAP-FAD-FA, which is a determinant of the results in the enzyme activity assay process in accumulating hydrocarbons. Meanwhile, the CvFAP enzyme activity assay results showed that the CvFAP enzyme extract from the KW21 medium treatment tended to produce pentadecane with a higher concentration than the CYT medium (2.8 times).  AbstrakMikroalga Chlorella variabilis menghasilkan enzim fatty acid photodecarboxylase (CvFAP) yang dapat mengkatalisis proses dekarboksilasi asam lemak rantai panjang menjadi biohidrokarbon melalui proses yang dipengaruhi oleh cahaya biru. Akan tetapi, kandungan enzim CvFAP pada C. variabilis relatif kecil dan kemampuan enzim tersebut sebagai biokatalis perlu dioptimasi.  Penelitian ini bertujuan untuk membandingkan pengaruh jenis medium kultivasi mikroalga C. variabilis, yaitu: 1) medium C, ekstrak ragi, dan tripton (medium CYT) dan 2) medium KW21 yang merupakan medium kultur alga komersial, terhadap pertumbuhan mikroalga dan protein yang dihasilkan. Selain itu, ekstrak enzim CvFAP dari tiap perlakuan medium diuji kemampuannya dalam mengkonversi asam lemak rantai panjang menjadi pentadekana melalui optimasi variasi jenis substrat, konsentrasi enzim, dan waktu inkubasi.   C. variabilis dikultivasi selama 2-3 minggu dengan rasio waktu pencahayaan terang dan gelap 8:16 (jam/ jam). Protein diekstrak secara fisika kimia dan uji aktivitas enzim dilakukan dalam kondisi diberi paparan cahaya biru.  Kandungan pentadekana yang terbentuk dari uji aktivitas enzim diukur menggunakan GC-MS. Hasil penelitian ini menunjukkan bahwa pertumbuhan mikroalga dan kandungan protein C. variabilis lebih tinggi pada medium CYT dibanding medium KW21. Band protein muncul tipis pada 67-68 kDA yang diduga dapat memengaruhi ikatan kompleks terner antara FAP-FAD-FA, yang merupakan penentu hasil pada proses uji aktivitas enzim dalam mengakumulasi hidrokarbon. Sementara itu, hasil uji aktivitas enzim CvFAP menunjukkan bahwa ekstrak enzim CvFAP dari perlakuan medium KW21 cenderung menghasilkan pentadekana dengan konsentrasi yang lebih tinggi dibanding medium CYT (2,8 kali lipat).